Sunitinib Treatment for Advanced Paraganglioma: Case Report of a Novel SDHD Gene Mutation Variant and Systematic Review of the Literature - Sesti, Franz; Feola, Tiziana; Puliani, Giulia; Centello, Roberta; Di Vito, Valentina; Bagni, Oreste; Lenzi, Andrea; Isidori, Andrea M.; Cantisani, Vito; Faggiano, Antongiulio; Giannetta, Elisa (Frontiers in Oncology, 2021)
Background. Paragangliomas (PGLs) are neuroendocrine neoplasms arising from chromaffin cells of sympathetic or parasympathetic paraganglia. Systemic therapies have been used only in metastatic PGLs. Antiangiogenic agents, such as sunitinib, could be a viable therapeutic choice in the subgroup of patients with SDH-positive PGLs. We describe the case of a man with Familial Paraganglioma Syndrome type 1 (FPGL) related to a novel mutation in SDHD gene treated with sunitinib. Furthermore, we performed a systematic review of the literature to investigate the effectiveness of sunitinib treatment in patients with advanced/progressive/metastatic PGL. Methods. We performed a data search using MEDLINE, Cochrane Library, and Scopus between April 2019 and September 2020. We included studies reporting data on clinical or biological characteristics, or clinical outcomes of patients with PGLs treated with sunitinib. Results. The search leaded to the selection of 25 publications. Data from case reports and case series showed that disease control rate (DCR = stable disease + partial response + complete response) was achieved in 34.7% of cases under suntinib treatment. In 39% of patients DCR was followed by progressive disease (PD) or tumor relapse, 26.1% patients showed PD. Data from clinical trials showed that DCR was 83%, and the median progression free survival was 13.4 months. Discussion. Sunitinib could be a viable therapeutic option in advanced/progressive/metastatic inoperable PGLs. However, further trials on the efficacy of sunitinib in FPGL and sporadic PGL are needed.